Job Insecurity on Job Performance with Subjective Wellbeing as a Mediating Variabel - Zannah, Nur Silvia; Syahrizal, Syahrizal (Universitas Negeri Padang, 2024)
Job performance is one of the most frequently researched phenomena in Human Resource Management (HRM) literature, job insecurity and subjective wellbeing being important managerial practices to research. However, the relationship between these practices has received little attention in the literature. Therefore, this study aims to examine the effect of job insecurity on job performance subjective wellbeing as a mediating variable. This research is a causal research. The sampling technique was taken using total sampling where the number of samples was the same as the population of 41 people. Data collection using a questionnaire with a Likert scale. The analysis technique used is SEM using SmartPLS4 analysis. The results of data processing. The results showed that job insecurity has a negative and significant effect on job performance through subjective wellbeing.